Take and read spiritual reading : an annotated list - Peterson, Eugene H., 1932- (Grand Rapids, MI Eerdmans, 1996)
Includes indexes.
Keywords: Spiritual life -- Christianity -- indexes; Spiritual life -- Christianity -- abstracts